Ethnicity-specific factors influencing childhood immunisation decisions among Black and Asian Minority Ethnic groups in the UK: a systematic review of qualitative research - Forster, Alice S (J Epidemiol Community Health, 2017)
BACKGROUND: Uptake of some childhood immunisations in the UK is lower among those from some Black and Asian Minority Ethnic (BAME) backgrounds. This systematic review of qualitative research sought to understand the factors that are associated with ethnicity that influence the immunisation decisions of parents from BAME backgrounds living in the UK. METHODS: Databases were searched on 2 December 2014 for studies published at any time using the terms ‘UK’ and ‘vaccination’ and ‘qualitative methods’ (and variations of these). Included articles comprised participants who were parents from BAME backgrounds. Thematic synthesis methods were used to develop descriptive and higher order themes. Themes specific to ethnicity and associated factors are reported. RESULTS: Eight papers were included in the review. Most participants were from Black (n=62) or Asian (n=38) backgrounds. Two ethnicity-related factors affected immunisation decisions. First, factors that are related to ethnicity itself (namely religion, upbringing and migration, and language) affected parents' perceived importance of immunisations, whether immunisations were permitted or culturally acceptable and their understanding of immunisation/the immunisation schedule. Second, perceived biological differences affected decision-making and demand for information. CONCLUSIONS: Factors related to ethnicity must be considered when seeking to understand immunisation decisions among parents from BAME backgrounds. Where appropriate and feasible, vaccination information should be targeted to address beliefs about ethnic differences held by some individuals from some BAME backgrounds.